Developing international strategies - Grünig, Rudolf; Morschett, Dirk (Springer, 2017)
This book helps medium-sized companies adapt to the challenges and take advantage of the opportunities of the growing international business climate. The authors offer practical, usable advice on production, sourcing and strategic planning.